2017
DOI: 10.1002/eji.201747089
|View full text |Cite
|
Sign up to set email alerts
|

Antigen presenting cell‐targeted proinsulin expression converts insulin‐specific CD8+ T‐cell priming to tolerance in autoimmune‐prone NOD mice

Abstract: Type 1 diabetes (T1D) results from autoimmune destruction of insulin-producing pancreatic β cells. Therapies need to incorporate strategies to overcome the genetic defects that impair induction or maintenance of peripheral T-cell tolerance and contribute to disease development. We tested whether the enforced expression of an islet autoantigen in antigen-presenting cells (APC) counteracted peripheral T-cell tolerance defects in autoimmune-prone NOD mice. We observed that insulin-specific CD8 T cells transferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This approach enables the delivery of antigens to DCs under steady-state conditions and the induction of peripheral tolerance ( 143 , 144 ). Reeves et al have shown that APC-targeted proinsulin expression converted insulin-specific CD8+ T-cell priming to tolerance in autoimmune-prone NOD mice ( 145 ). Ettinger et al achieved prolonged survival of transgenic mouse skin grafts by utilizing an antibody recognizing the CD205 receptor to deliver the immunodominant domain of type XVII collagen to host DCs without inflammatory stimuli ( 146 ).…”
Section: In Situ Targeting Of Dcregsmentioning
confidence: 99%
“…This approach enables the delivery of antigens to DCs under steady-state conditions and the induction of peripheral tolerance ( 143 , 144 ). Reeves et al have shown that APC-targeted proinsulin expression converted insulin-specific CD8+ T-cell priming to tolerance in autoimmune-prone NOD mice ( 145 ). Ettinger et al achieved prolonged survival of transgenic mouse skin grafts by utilizing an antibody recognizing the CD205 receptor to deliver the immunodominant domain of type XVII collagen to host DCs without inflammatory stimuli ( 146 ).…”
Section: In Situ Targeting Of Dcregsmentioning
confidence: 99%
“…The advantage of DC targeting is that non-myeloablative conditions permit substantial donor engraftment [526], as shown here, because the encoded neoantigen is not sensed before late DC differentiation. While no systematic comparisons of lineage-restricting promoters have been performed, more widely expressed and membrane-bound antigens appear to be more tolerogenic [247,255,567,636]. Other promoters that target other subsets of DC or APC may be equally effective as demonstrated elsewhere [528,548,549], indicating intrinsic differences in presentation that affect tolerogenic potential [538].…”
Section: Discussionmentioning
confidence: 99%
“…Analogous to the peripheral control of autoreactive B cells, T cells which escape negative selection are tolerised by deletion or functional inactivation in the periphery [245][246][247][248]. Chronic engagement with self-peptide-MHC presented by resting DC triggers clonal deletion [249,250].…”
Section: Peripheral T Cell Tolerance To Limit B Cell Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…[268]. Furthermore, other reports indicate that early intervention prevents pathogenic cells from expansion and acquisition of a memory phenotype [269,270] However, s.c. treatment of young 5-week-old mice did not delay the progression of T1D.…”
Section: Dmentioning
confidence: 99%